Exploring public perceptions of vaccine-derived poliovirus and a novel oral polio vaccine in the Democratic Republic of the Congo, Kenya, and Nigeria. (6th April 2023) - Lorenzetti, Lara; Haydarov, Rustam; Namey, Emily; Lawton, Anna; Nam, Hayon; Ridwan Hasan, Muhamad; Monj, Claude; Abeyesekera, Surangani; Amina Kabwau, Maria; McIntosh, Ross
Highlights: The introduction of nOPV2 requires a strategic communications plan. Awareness of cVDPV2 is low, but caregivers are concerned about repeat campaigns. Caregivers' concerns are linked to vaccine safety, efficacy, and side effects. Stakeholders felt caregivers would accept nOPV with adequate and timely information. Messaging should be consistent between trusted international and local authorities. Abstract: Background: The Global Polio Eradication Initiative introduced novel oral polio vaccine Type 2 (nOPV2) to address circulating vaccine-derived poliovirus Type 2 (cVDPV2). Although nOPV2 is a more genetically stable vaccine, it may not have the immediate trust of communities and health workers due to its novelty, potential side effects, and introduction under an Emergency Use Listing (EUL). We explored how nOPV2 introduction might be perceived by stakeholders and identified communications barriers related to nOPV2 hesitancy. Methods: This work was conducted in the Democratic Republic of the Congo, Kenya, and Nigeria between January and March 2020. We used a rapid qualitative approach to conduct focus group discussions and in-depth interviews with four stakeholder groups: caregivers of children under 5, polio frontline workers, healthcare practitioners, and social/health influencers. Data are presented according to awareness, attitudes/beliefs, and concerns about cVDPV2 and nOPV2. Results: Stakeholders were largely unaware of cVDPV2. The causes of recent polio outbreaks were characterized as poor sanitation, under-immunization/in-migration, or poor vaccine management procedures. Caregivers were aware of and concerned by repeated vaccination campaigns. All stakeholder groups anticipated initial hesitancy, fear, and suspicion from caregivers due to nOPV2 introduction, with primary concerns linked to vaccine testing, safety, effectiveness, side effects, and support from authorities. Stakeholders thought the term "genetic modification" could be controversial but that introduction under an EUL would be acceptable given the emergency nature of cVDPV2 outbreaks. Stakeholders called for adequate and timely information to counter concerns. Conclusions: Despite initial concerns, stakeholders felt nOPV2 would ultimately be accepted by caregivers. However, public health officials have a small window for "getting things right" when introducing nOPV2. Strategic communication interventions addressing key concerns and targeted communications with stakeholder groups, especially frontline workers, could improve community acceptance of nOPV2.